Pengolahan Limbah Pickling PT X dengan Metode Netralisasi KOH dan Filtrasi Granular untuk Menurunkan Kadar Fe²⁺: Indonesia - Aprivianti, Afif Nur; Perdani, Meka Saima; Aeni, Alfieta Rohmaful (Teknik Lingkungan Universitas Islam Indonesia, 2026)
Pickling effluent is characterized by highly acidic conditions and elevated Fe²⁺ levels, necessitating a treatment approach capable of achieving substantial metal removal prior to environmental discharge. In this work, neutralization was performed using Potassium Hydroxide (KOH) at concentrations of 20%, 40%, and 60%, accompanied by the addition of Polyacrylamide (PAM) at volumes of 20 mL, 40 mL, and 60 mL as a coagulant–flocculant. Stirring speeds (300, 600, and 900 rpm) and mixing durations (10, 15, and 20 minutes) were varied to determine the optimal conditions for floc formation and Fe²⁺ precipitation. Following the initial neutralization–precipitation stage, samples were subjected to granular filtration using a multi‑layer media system consisting of activated carbon, activated sand, ferrolite greensand, silica sand, and zeolite. The results indicate that the combination of 60% KOH and 60 mL PAM, with a stirring speed of 900 rpm for 20 minutes, yielded the highest Fe²⁺ reduction, decreasing concentrations from 160 g/L to 46.13 g/L. Subsequent granular filtration further reduced Fe²⁺ to undetectable levels based on titration analysis. Additionally, the final effluent pH Fe²⁺ll within the neutral range, meeting applicable environmental quality standards.